Overview of Nutritional Fulfillment in Dm-TB Patients At the Gorontalo City Health Center - Mahirnawati A. Giso; Zainuddin; Muh. Syukriani Yusuf (Universitas Muhammadiyah Palu, 2026)
Diabetes Mellitus (DM) and Tuberculosis (TB) are interrelated diseases and can worsen patients' health conditions. DM-TB patients are at risk of impaired nutritional fulfillment due to increased energy needs, decreased appetite, and metabolic disorders of the body. Adequate nutritional fulfillment is important to support the healing process, increase immunity, and help control blood sugar levels. This study aims to find out the picture of nutritional fulfillment in DM-TB patients at the Gorontalo City Health Center. The research uses a quantitative method with a descriptive design. The research was carried out in 6 Gorontalo City Health Centers, namely Dungingi Health Center, Central City, West City, Sipatana, North City, and South City from December 29, 2025 to January 26, 2026. The study sample was DM-TB patients selected using total sampling techniques. Data collection was conducted using the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) to assess nutritional fulfillment based on energy intake, carbohydrates, proteins, fats, and micronutrients. The data were analyzed univariately and presented in frequency distributions. The results of the study showed that most of the respondents had not yet optimal nutritional fulfillment. The conclusion of this study is that the fulfillment of nutrition in DM-TB patients at the Gorontalo City Health Center still needs to be improved through nutrition education and proper dietary assistance.